Kraft pulping using juvenile Acacia Mangium - Draman, Asri; Mohamad, Azlan; Mohd Nor, Mohd Khaidir; Zakaria, Mohd Nor Zainuddin (2010)
This research done to see the potential of juvenille acacia mangium in producing paper using kraft pulping. We have used three different of percentage of active alkali that is 16%, 18%, and 20% and different beating revolution that is 0, 5000, and 10000 rpm. This study show that the increasing in active alkali increase the mechanical strength of paper like tensile and tearing but the bulk properties is reduce. The beating revolution also increase the tensile and tearing strength of paper but reduce the bulk.